Psychometric validation of the reintegration to normal living index in people living with spinal cord injuries - D.J. Mothabeng; C.A. Eksteen; M. Westaway (AOSIS, 2012)
The evaluation of rehabilitation outcomes requiresmeasurementinstruments that are valid and reliable, and have been psychometricallytested in the context of a particular population. The purpose ofthis study was to psychometrically test the validity and reliability of theReintegration to Normal Living Index (RNLI) as a measure of communityreintegration in a population of community-dwelling people living withspinal cord injury (PLWSCI) in South Africa.The study was a cross-sectional, involving community dwelling peopleliving with SCI (PLWSCI), who had been discharged from inpatient rehabilitation at for at least two years. RNLI datacollected from 160 PLWSCI were subjected to factor analysis and tested for reliability using chronbach's alpha.Cronbach's alpha for the RNLI instrument was 0.97 (ICC 95% CI: 0.97 - 0.98), indicating an excellent reliabilitycoefficient. A single -factor structure emerged from principal components analysis, indicating that there is onlyone factor structure for the RNLI in this population of PLWSCI. The content, construct, convergent and discriminatevalidity of the instrument were established.The results of this study support the reliability and factorial validity of the RNLI as a measure of community reintegrationfor PLWSCI. The RNLI is therefore a valuable outcome measure and should be extended to other SCIrehabilitation studies in South Africa.